Theory: Morphological and functional features of the structure of the Zonula Lens Fibers as a key executive link in the mechanism of the human eye accommodation - Ivan N Koshits; Olga V Svetlova; Maksat B Egemberdiev; Marina G Guseva; Felix N Makarov; Nikolas M Roselo Kesada (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Purpose: Assess morphophysiological and functional features of the structure of the zonula lens fibers on the basis of an in-depth analysis consistent with the laws of mechanics. Define the purpose and scope of each portion of the zonula lens fibers. To analyze the results of the research of studies on the structure of the zonula of Zinn in the different authors of the last two centuries. Identify misconceptions about the work of this executive mechanism of accommodation in different phases of accommodation, this includes the uneven accommodation in different meridians. Determine the incorrectness of those theories of accommodation, which are based on erroneous ideas about the functioning of different portions of the zonula fibers. Methods: Theoretical analysis based on the laws of mechanics and assessment of the results of interdisciplinary research by different authors in the field of structural and functional features of the Zinn's zonule of the lens in different phases of accommodation. Results: The lens's ciliary belt has been found to have three major portions of fiber that perform different functions. Powerful anterior portion of fibers is attached to the anterior surface of the lens bag in a segmented mannered a powerful posterior portion of fibers is attached to the posterior surface of the lens evenly around the circumference and like a cobweb covering the surface of the vitreous chamber. Both these filaments in the eye don't cross and in all phases of accommodation remain tense: in full distance - maximum, and when you look close, it's minimal. These functional features of two powerful portions of the zonula of Zinn are fully consistent with Helmholtz's vision and allows them to hold the lens relative to the optical axis of the eye even under high dynamic or weightless conditions. These two portions of fiber are force-bearing and constantly press the lens against the vitreous chamber, fixing its normal position relative to the optical axis. It is characteristic that both these powerful portions of fibers pass in the direction of the choroid through the recesses between the processes of the ciliary muscle. It is important that both of these portions of fibers are not attached to the ciliary muscle by force, but are only held by the thinnest outlet fibers in the recesses between its processes. The anterior and posterior portions of the fibers are attached forcefully to the anterior of the lens bag, and behind they are attached to the choroid in the ora serrata region. The segmental attachment of the anterior portion of the fibers to the lens bag allows for uneven lens accommodation in different meridians. The third portion of ciliary zonula fibers - cilio-equatorial fibers, on the contrary, is not strong and is located evenly along the equator of the lens. Two rows of these thin fibers on one side are attached in the form of a frenum evenly along the equator of the lens bag, and on the other side they are attached directly to the ciliary muscle in the recesses between its processes. The task of these fibers is to uniformly collapse around the extreme periphery of the lens bag in the equator region to keep the lens masses near the optical axis, preventing them from shifting to the equator inside the lens bag during different phases of accommodation. Conclusion: Analysis of the morphophysiological structure of the Zinn's zonule of the lens, adequate to the laws of mechanics, made it possible to deepen and expand the classical theory of lens accommodation H. Helmholtz - where the lens is the main, but not the only mechanism of accommodation in the human eye. It was found that the executive mechanisms in the lens accommodation are: ciliary muscle, zonula of Zinn, vitreous chamber and choroid. The choroid is a biological spring and passively stretches the ciliary muscle depending on the level of its active tone. In all phases of accommodation, the lens is pressed by a powerful anterior portion of fibers to the hyaloid membrane of the vitreous chamber. At moments of external dynamic loads on the eye, the energy of inertial micro movements or the lens phacodonesis is transferred to the vitreous chamber, which dampens these vibrations due to the dispersion of this energy between its internal structures. These ideas are adequate to the laws of mechanics and exactly correspond to Helmholtz formulations: in all phases of accommodation, the anterior and posterior portions of the fibers remain stretched and their tension only slightly relaxes when looking completely closer. The detected segmented attachment of the anterior portion of the fibers to the anterior part of the lens capsule allows for uneven accommodation in different meridians to partially level the induced astigmatism of the optical system of the eye under different visual loads. The most important result was the understanding that the pressure in the lens is at maximum when viewed completely closer. This leads to the extension and rounding of the anterior and posterior mini lens of the lens and increase their refractive power for rays passing near the optical axis of the eye. On the contrary, when looking completely into the distance, the choroid stretches the anterior and posterior portions of the fibers as much as possible, due to which the lens bag is maximally stretched, and the lens itself becomes flatter.At this moment, the pressure in the lens is minimal, since the elastic capsule of the lens is stretched from the outside by the zonula fibers and therefore compresses the intralenticular masses the weakest of all with less force. It is at this moment that the work of the cilio-equatorial fibers is necessary in order to evenly squeeze the periphery of the lens along the entire equator and keep the lens masses in the center of the optical axis. The results also confirmed the incorrectness of many theories of accommodation compared to Helmholtz's theory of accommodation. Especially incorrect seems the extravagant theory of accommodation R.A. Shachar.